TrypOx, a Novel Eukaryotic Homolog of the Redox-Regulated Chaperone Hsp33 in Trypanosoma brucei - Aramin, Samar; Fassler, Rosi; Chikne, Vaibhav; Goldenberg, Mor; Arian, Tal; Kolet Eliaz, Liat; Rimon, Oded; Ram, Oren; Michaeli, Shulamit; Reichmann, Dana (Frontiers in Microbiology, 2020)
ATP-independent chaperones are widespread across all domains of life and serve as the first line of defense during protein unfolding stresses. One of the known crucial chaperones for bacterial survival in a hostile environment (e.g. heat and oxidative stress) is the highly conserved, redox-regulated ATP-independent bacterial chaperone Hsp33. Using a bioinformatic analysis, we describe novel eukaryotic homologues of Hsp33 identified in eukaryotic pathogens belonging to the kinetoplastids, a family responsible for lethal human diseases such as Chagas disease as caused by Trypanosoma cruzi, African sleeping sickness caused by Trypanosoma brucei spp, and leishmaniasis pathologies delivered by various Leishmania species. During their pathogenic life cycle, kinetoplastids need to cope with elevated temperatures and oxidative stress, the same conditions which convert Hsp33 into a powerful chaperone in bacteria, thus preventing aggregation of a wide range of misfolded proteins. Here we focused on a functional characterization of the Hsp33 homologue in one of the members of the kinetoplastid family, T. brucei, (Tb927.6.2630), which we have named TrypOx. RNAi silencing of TrypOx led to a significant decrease in the survival of T.brucei under mild oxidative stress conditions, implying a protective role of TrypOx during the Trypanosomes growth. We then adopted a proteomics-driven approach to investigate the role of TrypOx in defining the oxidative stress response. Depletion of TrypOx significantly altered the abundance of proteins mediating redox homeostasis, linking TrypOx with the antioxidant system. Using biochemical approaches, we identified the redox-switch domain of TrypOx, showing its modularity and oxidation-dependent structural plasticity. Kinetoplastid parasites such as T.brucei need to cope with high levels of oxidants produced by the innate immune system, such that parasite-specific antioxidant proteins like TrypOx – which are depleted in mammals – are highly promising candidates for drug targeting.